Stimulation of hepatocarcinogenesis by activated cholangiocytes via Il17a/f1 pathway in kras transgenic zebrafish model - Helal, Mohamed (Sci Rep, 2021)
It has been well known that tumor progression is dependent on secreted factors not only from tumor cells but also from other surrounding non-tumor cells. In the current study, we investigated the role of cholangiocytes during hepatocarcinogenesis following induction of oncogenic kras(V12) expression in hepatocytes using an inducible transgenic zebrafish model. Upon induction of carcinogenesis in hepatocytes, a progressive cell proliferation in cholangiocytes was observed. The proliferative response in cholangiocytes was induced by enhanced lipogenesis and bile acids secretion from hepatocytes through activation of Sphingosine 1 phosphate receptor 2 (S1pr2), a known cholangiocyte receptor involving in cholangiocyte proliferation. Enhancement and inhibition of S1pr2 could accelerate or inhibit cholangiocyte proliferation and hepatocarcinogenesis respectively. Gene expression analysis of hepatocytes and cholangiocytes showed that cholangiocytes stimulated carcinogenesis in hepatocytes via an inflammatory cytokine, Il17a/f1, which activated its receptor (Il17ra1a) on hepatocytes and enhanced hepatocarcinogenesis via an ERK dependent pathway. Thus, the enhancing effect of cholangiocytes on hepatocarcinogenesis is likely via an inflammatory loop.